Positive electrode material lithium-containing precursor and preparation method thereof, positive electrode material and lithium secondary battery

Preparation of lithium-containing oxide precursors through atomization and calcination treatment solves the problems of medium and high cost and environmental protection in the preparation of traditional positive electrode materials, improves the distribution uniformity of lithium and material stability, and achieves efficient and environmentally friendly positive electrode materials production.

CN119191374APending Publication Date: 2024-12-27HUNAN LEAGUER HOPE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310754274.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There are high cost and environmental protection problems in the preparation process of traditional cathode materials, especially the co-precipitation method of hydroxide precursors, which leads to difficulties in wastewater treatment, and the uneven distribution of lithium affects electrochemical performance.

Method used

A lithium-containing oxide precursor and its preparation method were developed. The positive electrode material precursor was prepared by atomization and calcination treatment, which avoided the generation of hydroxide, improved the distribution uniformity of lithium and the structural stability of the material, and simplified the Production process.

Benefits of technology

It reduces the manufacturing cost of positive electrode materials, improves yield and electrochemical performance, reduces carbon emissions, and solves the problem of raw material supply stability, achieving a more efficient and environmentally friendly production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191374A_ABST
    Figure CN119191374A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material lithium-containing precursor and a preparation method thereof, a positive electrode material and a lithium secondary battery. The lithium-containing precursor of the positive electrode material meets the chemical formula Lia (Ni < x > Co < y > Mn < 1-x-y >) O (1 + a) (Li < 2 > CO < 3 >) z, wherein a is 0.10-1.08; 0 < x < 1, 0 < y < 1, and x + y < 1; z is greater than 0 and less than or equal to 0.354, and the carbon content is greater than 0 and less than or equal to 6.2 wt%. According to the lithium-containing precursor of the positive electrode material disclosed by the invention, lithium is directly pre-sintered into the precursor, so that the production process flow of the positive electrode material is simplified; decomposition of lithium carbonate into carbon dioxide is reduced, and carbon emission is reduced; lithium is directly pre-sintered into the precursor, so that the loss rate of lithium during sintering of the positive electrode material is reduced, the yield of finished products under the same bowl loading amount is improved, and the productivity of a production line is greatly increased; in addition, when the lithium-containing precursor of the positive electrode material is sintered, excessive waste water is not generated, so that the lithium-containing precursor of the positive electrode material provided by the invention is more economical and more environment-friendly compared with a traditional precursor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for lithium batteries, and in particular to a positive electrode material containing lithium precursor and a preparation method thereof, a positive electrode material and a lithium secondary battery. Background Art

[0002] With the rapid development of new energy vehicles, the demand for power batteries is increasing, but it is also facing greater challenges. In addition, power batteries account for a high proportion of the cost of new energy vehicles, and positive electrode materials account for more than 60% of the cost of battery cells. The industry has always hoped to reduce the cost of producing positive electrode materials.

[0003] In power batteries, the preparation of traditional positive electrode materials is to mix the positive electrode material precursor with the lithium source and then sinter it multiple times. Therefore, the precursor determines the performance and cost of the positive electrode material. For example, the traditional hydroxide precursor is prepared by co-precipitation, which is easy to produce wastewater, and treating wastewater is neither economical nor environmentally friendly.

[0004] Therefore, there is still a need to develop a new positive electrode material precursor and / or positive electrode material and production process. Summary of the invention

[0005] The present inventors have developed a positive electrode material lithium-containing precursor and a preparation method thereof, a positive electrode material and a lithium secondary battery through intensive research, thereby overcoming one or more of the above-mentioned deficiencies of the prior art.

[0006] The present disclosure provides a first aspect of a positive electrode material containing lithium precursor, which satisfies the chemical formula Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , wherein a is 0.10 to 1.08; 0<x<1, 0<y<1, and x+y<1; z is greater than 0 and less than or equal to 0.354, and its carbon content is greater than 0 and less than or equal to 6.2 weight %.

[0007] The lithium-containing precursor of the positive electrode material disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no waste water is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with a traditional hydroxide precursor, the oxide precursor has a higher content of main metals of nickel, cobalt and manganese. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the loss rate of lithium during sintering of the positive electrode material is reduced, and the yield of finished products under the same loading amount is increased, thereby increasing the output when sintering into a positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity.

[0008] The second aspect of the present disclosure provides a method for preparing a lithium-containing precursor of a positive electrode material, comprising the following steps:

[0009] preparing a mixed solution of lithium nitrate, nickel nitrate, cobalt nitrate and manganese nitrate;

[0010] The mixed solution is subjected to atomization calcination treatment to obtain the aforementioned positive electrode material lithium-containing precursor, the temperature of the atomization calcination treatment is 400° C.-1000° C., and the air-to-coal ratio of the calcination furnace is less than 10.

[0011] Since the preparation method prepares the aforementioned lithium-containing precursor, therefore, the preparation method of the lithium-containing precursor also inherits the technical effect of the lithium-containing precursor; at the same time, the lithium-containing precursor in the present application is formed by atomization roasting. Compared with the hydroxide precursor prepared by the coprecipitation method, the process flow of the present application is simple, the intermediate process is small, the reaction process is convenient for flexible regulation, and the roasting treatment is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also the product has a fast reaction speed. The actual reaction time of atomization roasting to obtain the lithium-containing precursor material is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high temperature environment to be removed or recycled, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent. At the same time, the lithium-containing precursor material product prepared by this method has a better structural stability of the material itself than the traditional coprecipitation method.

[0012] A third aspect of the present disclosure provides a positive electrode material, which is formed by sintering the aforementioned positive electrode material-containing lithium precursor.

[0013] A fourth aspect of the present disclosure provides a method for preparing a positive electrode material, which is formed by maintaining the aforementioned positive electrode material precursor at a first temperature of 400°C-800°C for 1-5 hours and maintaining it at a second temperature of 800°C-1050°C for 5-10 hours before sintering.

[0014] Since the positive electrode material is sintered from the aforementioned lithium-containing precursor, the positive electrode material also inherits the technical effects of the lithium-containing precursor; when the hydroxide precursor is used to prepare the positive electrode material, the positive electrode hydroxide precursor usually needs to be mixed with a lithium source in a solid state and then sintered at a high temperature. However, due to the uneven mixing between solids and the slow diffusion rate of lithium in the solid phase, it may be difficult to evenly distribute lithium. The uneven distribution of lithium will seriously affect the electrochemical properties of the positive electrode material. When the lithium-containing precursor of the present application is used to prepare the positive electrode material, since the lithium-containing precursor itself has lithium, when preparing the positive electrode material, only a small amount of lithium source needs to be added or no lithium source needs to be added to directly sinter it into the positive electrode material, so that the distribution of lithium is more uniform and the electrochemical properties of the positive electrode material are improved. On the other hand, by directly pre-burning lithium into the precursor, the subsequent mixing process of the precursor and the lithium source is reduced, and the production process of the positive electrode material is simplified; relative to the traditional precursor and lithium carbonate sintering process, the decomposition of lithium carbonate into carbon dioxide is reduced, and carbon emissions are reduced; due to the direct pre-burning of lithium into the precursor, the temperature of the lithium-containing precursor of the present application when sintering the positive electrode material is lower than the temperature of the traditional precursor sintering the positive electrode material under the same conditions, so the sintering cost can be reduced. On the other hand, since the positive electrode material precursor supplier and the lithium source supplier are usually independent of each other, the downstream positive electrode material manufacturers need to strictly control the product quality and batch stability of the positive electrode material precursor supplier and the lithium source supplier, which is difficult, which is not conducive to the stability of the preparation of the positive electrode material. The lithium-containing precursor of the present application itself has lithium, therefore, to a certain extent, the raw material supply problem of the positive electrode material manufacturer is solved, and the stability of the preparation of the positive electrode material is improved.

[0015] A fourth aspect of the present disclosure provides a secondary battery, wherein a positive electrode sheet of the secondary battery includes the positive electrode material.

[0016] Since the lithium secondary battery contains the aforementioned positive electrode material, the lithium secondary battery also inherits the technical effects of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0018] Figure 1 This is a SEM photograph of the lithium-containing precursor of the positive electrode material of Example 1 of the present disclosure at a magnification of 1000.

[0019] Figure 2 This is a SEM photograph of the lithium-containing precursor of the positive electrode material of Example 1 of the present disclosure at a magnification of 20.0K.

[0020] Figure 3This is a SEM photograph of the lithium-containing precursor of the positive electrode material of Example 1 of the present disclosure at a magnification of 50.0K.

[0021] Figure 4 This is the XRD spectrum of the lithium-containing precursor of the positive electrode material of Example 1 of the present disclosure.

[0022] Figure 5 This is a SEM photograph of the positive electrode material of Example 1 of the present disclosure.

[0023] Figure 6 This is the XRD spectrum of the positive electrode material of Example 1 of the present disclosure. DETAILED DESCRIPTION

[0024] The present invention may be implemented in other specific forms without departing from the basic attributes of the present invention. It should be understood that, without conflict, any and all embodiments of the present invention may be combined with the technical features in any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes other embodiments obtained by such combination.

[0025] All publications and patents mentioned in this disclosure are hereby incorporated by reference into this disclosure in their entirety. If the purposes or terms used in any publications and patents incorporated by reference conflict with the purposes or terms used in this disclosure, then the purposes and terms of this disclosure shall prevail.

[0026] The section headings used herein are for organizational purposes only and are not to be construed as limiting the subject matter described.

[0027] Unless otherwise specified, all technical and scientific terms used herein have the common meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.

[0028] Except in the working examples or otherwise indicated, all numbers stating quantitative properties such as particle size in the specification and claims should be understood to be modified by the term "about" in all cases. It should also be understood that any numerical range recited in this application is intended to include all subranges within the range and any combination of the various endpoints of the range or subrange.

[0029] The words "include", "contain" or "comprises" and the like used in the present disclosure mean that the elements preceding the word include the elements listed after the word and their equivalents, without excluding unrecorded elements. The terms "contain" or "includes" used herein may be open, semi-closed and closed. In other words, the term also includes "consisting essentially of" or "consisting of".

[0030] The term "optionally" in this disclosure means that the described circumstances may or may not occur.

[0031] The term "positive electrode material precursor" in the present disclosure refers to the substance before the high temperature sintering step in the process of preparing the positive electrode material (hereinafter sometimes referred to as "precursor" or "precursor"). The term "positive electrode material lithium-containing precursor" refers to the aforementioned positive electrode material precursor containing lithium.

[0032] Unless otherwise specified, the term "Li" does not refer to Li metal alone but to Li element. The same applies to expressions of other elements such as Ni, Co, and Mn.

[0033] <Positive electrode material containing lithium precursor>

[0034] The first aspect of the present disclosure provides a positive electrode material containing lithium precursor, which comprises an oxide of lithium nickel cobalt manganese and lithium carbonate. In one embodiment, the positive electrode material containing lithium precursor is substantially composed of an oxide of lithium nickel cobalt manganese and lithium carbonate. For example, the total weight of the oxide of lithium nickel cobalt manganese and lithium carbonate in the positive electrode material containing lithium precursor accounts for more than 96.0% by weight of the precursor, for example, more than 97.0% by weight, more than 98.0% by weight, more than 99.0% by weight, more than 99.1% by weight, more than 99.2% by weight, more than 99.3% by weight, more than 99.4% by weight, more than 99.5% by weight, more than 99.6% by weight, more than 99.7% by weight, more than 99.8% by weight, more than 99.9% by weight.

[0035] The precursor in the prior art does not contain lithium. When the precursor is prepared into a positive electrode material, the precursor needs to be mixed with a lithium source first, and then the precursor and the lithium source are placed in a roasting furnace for sintering, so that the lithium in the lithium source enters the molecular structure to form a positive electrode material. However, the lithium-containing precursor of the present application contains lithium. When the lithium-containing precursor is used to prepare a positive electrode material, it is not necessary to add a lithium source or only a small amount of lithium source is added to sinter the positive electrode material.

[0036] The precursor in the present application contains lithium and is represented by the following formula (I):

[0037] Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z (I)

[0038] Wherein a is 0.10-1.08; 0<x<1, 0<y<1, and x+y<1; z is greater than 0 and less than or equal to 0.354, a, x, y, z are expressed in mol, and the carbon content is greater than 0 and less than or equal to 6.2 weight %.

[0039] Taking into account that sufficient lithium is burned into the lithium-containing precursor, the carbon content is preferably above 0.05 weight %. Taking into account that when the lithium-containing precursor is sintered into a positive electrode material, too much carbon will form free lithium, which will affect the electrochemical performance of the lithium-containing precursor when used in a lithium secondary battery, the lithium content of the carbon is below 6.2 weight %.

[0040] In a preferred embodiment, the carbon content in the lithium-containing precursor of the positive electrode material is preferably 0.05% to 2.0% by weight, for example, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2.0% by weight.

[0041] Selecting a carbon content of 0.05 wt % to 2.0 wt % can not only ensure that the lithium-containing precursor has sufficient lithium, but also prevent the positive electrode material from forming too much free lithium and reduce carbon emissions during the sintering process.

[0042] From the viewpoint of obtaining a lithium secondary battery with high reversible capacity, x in the above formula (I) is preferably 0.5 or more, more preferably 0.55 or more, and particularly preferably 0.8 or more. In addition, from the viewpoint of obtaining a lithium secondary battery with higher initial charge and discharge efficiency, it is preferably less than 1.0, more preferably 0.95 or less, and particularly preferably 0.9 or less.

[0043] The upper limit and lower limit of x may be arbitrarily combined. For example, x is preferably 0.4 or more and less than 1.0, more preferably 0.50 or more and 0.90 or less, and further preferably 0.55 or more and 0.80 or less.

[0044] Specifically, x can be selected as 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, and 0.90.

[0045] In addition, from the viewpoint of obtaining a lithium secondary battery with low battery resistance, y in the above formula (I) is preferably 0.01 or more, and more preferably 0.05 or more. In addition, from the viewpoint of obtaining a lithium secondary battery with high thermal stability, y is preferably 0.40 or less, more preferably 0.29 or less, and more preferably 0.20 or less.

[0046] The upper limit and lower limit of y may be arbitrarily combined. For example, y is 0.01 or more and 0.40 or less, more preferably 0.01 or more and 0.29 or less, and further preferably 0.05 or more and 0.20 or less.

[0047] Specifically, y can be selected as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, and 0.40.

[0048] In addition, from the viewpoint of obtaining a lithium secondary battery with high thermal stability, 1-xy in the above composition formula (I) is preferably 0.01 or more, and more preferably 0.05 or more. In addition, from the viewpoint of obtaining a lithium secondary battery with high storage characteristics under high temperature (for example, 60°C environment), 1-xy in the above composition formula (I) is preferably 0.40 or less, more preferably 0.30 or less, and more preferably 0.18 or less.

[0049] Specifically, 1-xy can be selected to be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40.

[0050] In a preferred embodiment, the positive electrode material contains a lithium precursor having the chemical formula Li a (Ni x Co y Mn 1-x-y )O2(Li2CO3)z Among them, 0.55≤x≤0.80, 0.05≤y≤0.20, 0.08≤1-xy≤0.30.

[0051] In addition, from the perspective of shortening the process and improving the finished product yield under the same loading amount, a in the above-mentioned composition formula (I) is preferably more than 0.10, more preferably more than 0.50, and more preferably more than 1.0. In addition, from the perspective of maintaining a lithium secondary battery with high cycle performance, a in the above-mentioned composition formula (I) is preferably less than 1.2, more preferably less than 1.1, and more preferably less than 1.08.

[0052] Specifically, the value range of a is 1<a≤1.08. In this way, the lithium-containing precursor of the positive electrode material can be sintered to prepare the positive electrode material without mixing with another lithium source. This reduces the process of mixing the precursor with the lithium source, thereby reducing costs. At the same time, since the lithium-containing precursor already has sufficient lithium, when sintering into the positive electrode material, the loss rate of lithium can be reduced, and the yield of the finished product at the same loading amount can be improved. In a more preferred embodiment, the value of a in (I) is 1.01~1.06. This can further reduce the loss rate of lithium when the precursor is sintered into the positive electrode material, and improve the yield of the finished product at the same loading amount.

[0053] If 0.10≤a≤0.50, then when preparing the precursor, the recycled material obtained from waste lithium batteries can be used. The recycled material contains a small amount of lithium, and the recycled material is used as a raw material to prepare the lithium-containing precursor, which can reduce the loss rate of lithium and reduce production costs. If 0.50≤a≤1.00, then when preparing the positive electrode material, only a small amount of lithium source needs to be added. The positive electrode material prepared using the lithium-containing precursor in this range has less free lithium, which is beneficial to improving the electrochemical performance of the positive electrode material.

[0054] Specifically, a can be selected from 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0. 33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.5 8, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83 , 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, etc.

[0055] Taking into account the difficulty and cost of the precursor preparation and the subsequent preparation of the positive electrode material, 0.05≤z≤0.20 is preferred.

[0056] By adjusting the ratio of each metal element in the lithium-containing precursor, the lithium secondary battery can have higher initial charge and discharge efficiency, improved finished product yield under the same loading amount, simpler process and higher thermal stability.

[0057] For example, you can choose

[0058] Li 0.72 (Ni 0.55 Co 0.23 Mn 0.22 ) 1.72 (Li2CO3) 0.15 , Li 0.72 (Ni 0.67 Co 0.05 Mn 0.28 ) 1.72 (Li2CO3) 0.15 , Li 0.62 (Ni 0.80 Co 0.10 Mn 0.10 ) 1.62(Li2CO3) 0.20 , Li 0.70 (Ni 0.77 Co 0.13 Mn 0.10 ) 1.70 (Li2CO3) 0.15 , Li 0.70 (Ni 0.90 Co 0.05 Mn 0.05 ) 1.70 (Li2CO3) 0.15 wait.

[0059] [Composition Analysis]

[0060] The composition analysis of the lithium-containing precursor is to add the obtained powder of the lithium-containing precursor into a 100mL beaker, add 6mL of hydrochloric acid and 2mL of nitric acid for digestion, filter after cooling (if necessary), and dilute to a 250mL volumetric flask, use a 5mL large-bellied pipette to take 5mL to a 100mL volumetric flask, add 2mL of nitric acid, dilute to volume, and use Thermo Fisher ICP-OES to test the contents of Li, Ni, Co, Mn, etc.

[0061] Use Wanlianda CS-901B high-frequency infrared carbon-sulfur instrument to test the carbon content (instrument manufacturer: Wanlianda, model: CS-901B6). Impurity test: burn the ceramic crucible at 900℃ for 4h and then cool it to room temperature. First test 3 sets of standard samples for calibration, then weigh 0.4±0.01g of iron flux in the crucible, return to zero, and then weigh a certain amount of lithium-containing precursor sample, add a spoonful of tungsten particles, test the lithium-containing precursor sample on the machine, click analysis, and output the data.

[0062] The lithium-containing precursor of the positive electrode material disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no waste water is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with a traditional hydroxide precursor, the content of the main metals of nickel, cobalt and manganese in the oxide precursor is higher. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the loss rate of lithium during sintering of the positive electrode material is reduced, and the yield of the finished product under the same loading amount is improved, thereby increasing the output when sintering into the positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity.

[0063] In one embodiment, the positive electrode material lithium-containing precursor includes at least one sheet-like agglomerate formed by agglomeration of primary particles.

[0064] It should be noted that the lithium-containing precursor may include a plurality of flaky agglomerates, and there are gaps between the flaky agglomerates, and the gaps are 1 nm to 1 μm. For example, the lithium-containing precursor includes 2 flaky agglomerates, 3 flaky agglomerates, 4 flaky agglomerates, and the like. The number of flaky agglomerates is not specifically limited in the embodiments of the present application.

[0065] For example, through SEM observation, the positive electrode material containing lithium precursor after the sphere is crushed is irregular flake, and the maximum thickness of the flake agglomerate is 0.1-7 μm, the maximum length is 0.1-19 μm, and the maximum width is 0.1-19 μm. In order to improve the electrode density when the positive electrode for lithium secondary batteries is made, the volume capacity density is improved, as a preferred method, the maximum thickness of the flake agglomerate is 0.2-6 μm, the maximum length is 1.0-15 μm, and the maximum width is 1.0 μm-15 μm. In order to further improve the electrode density when the positive electrode for lithium secondary batteries is made, the volume capacity density is improved, and it is more preferred that the maximum thickness of the flake agglomerate is 2-5 μm, the maximum length is 3-10 μm, and the maximum width is 3 μm-10 μm. Specifically, the maximum thickness of the flake agglomerate can be selected as 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, etc. Specifically, the maximum length of the flake aggregates can be selected to be 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 15 μm, 19 μm, etc. Specifically, the maximum width of the flake aggregates can be selected to be 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 15 μm, 19 μm, etc.

[0066] When using the positive electrode material manufactured by the lithium-containing precursor of the present application, since crystal growth is not excessive, the mobile resistance of lithium ions is not easy to increase. The precursor of the present application is used to manufacture the positive electrode material, which is easy to form a state in which lithium ions are evenly distributed in the particles. The lithium ion conductivity of such a positive electrode material is easily improved. When using such a positive electrode material, the cycle maintenance rate of the lithium secondary battery can be improved.

[0067] Conventional ternary hydroxide precursor materials are usually spherical or quasi-spherical when observed through SEM after the spheres are broken.

[0068] In the present application, the term "primary particles" refers to particles that have no crystal grain boundaries in appearance when observed at a viewing angle of 5,000 to 20,000 times using a scanning electron microscope or the like.

[0069] In the present application, the term "agglomerate" refers to particles formed by agglomeration of the primary particles described above, and a flake-like agglomerate further refers to particles having a flake-like or substantially flake-like shape.

[0070] [SEM measurement]

[0071] The morphology of the material was observed using a tungsten filament scanning electron microscope (VEGA LMS, produced by Tescan). The SEM observation was performed using electron beams with an acceleration voltage of 10kev and a working distance of 5mm.

[0072] In one embodiment, the positive electrode material containing lithium precursor is a sheet-like agglomerate, and the agglomerate is agglomerated by a plurality of primary particles of less than 100 nanometers. In order to improve the electrode density when the positive electrode for lithium secondary battery is made, the volume capacity density is improved, preferably, the primary particles are less than 90 nanometers, and more preferably, the primary particles are less than 80 nanometers and more than 50 nanometers. Specifically, the particle size of the primary particles can be 100nm, 90nm, 80nm, 70nm, 60nm, 50nm, etc.

[0073] Primary particles are less than 100 nm, and there are few interfaces between primary particles, so the particles of the positive electrode material are not easy to crack during charging and discharging. The positive electrode material produced by using the lithium-containing precursor of this embodiment as a raw material is not easy to generate resistance, so the cycle retention rate of the lithium secondary battery can be improved.

[0074] The lithium-containing precursor of the cathode material disclosed in the present invention has a diffraction peak at 31.7±0.3 degrees 2θ in a powder x-ray diffraction pattern using Cu-Kα radiation, which is believed to be a characteristic peak of lithium carbonate, indicating that the precursor contains lithium carbonate.

[0075] In one embodiment, the powder x-ray diffraction pattern of the positive electrode material lithium-containing precursor using Cu-Kα radiation has diffraction peaks at 18.6±0.3, 21.2±0.3, 30.5±0.3, 31.7±0.3, 36.4±0.3, 38.0±0.3, 44.1±0.3, 48.4±0.3, 58.3±0.3, 64.2±0.3, and 67.7±0.3 degrees 2θ.

[0076] In the lithium-containing precursor of the present application, in the powder x-ray diffraction pattern using Cu-Kα rays, there are diffraction peaks at 2θ=48.4±0.3, 2θ=58.3±0.3, and 2θ=67.7±0.3 degrees, indicating that lithium has been pre-burned into the lithium-containing precursor in the present application. Since the lithium-containing precursor already has lithium, when the lithium-containing precursor is used to prepare the positive electrode material, the process of mixing the precursor with the lithium source is reduced, and the production of the positive electrode material is simplified. Production process flow; compared with the traditional precursor and lithium carbonate sintering process, the decomposition of lithium carbonate into carbon dioxide is reduced, thereby reducing carbon emissions; since lithium is directly pre-burned into the precursor, the lithium loss rate during the sintering of the positive electrode material is reduced, thereby improving the finished product yield under the same loading amount and greatly increasing the production line capacity; in addition, when the lithium-containing precursor in the present application is sintered, the temperature of the lithium-containing precursor in the present application when sintering the positive electrode material is lower than that of the traditional precursor under the same conditions, thereby reducing the sintering cost.

[0077] [Powder X-ray diffraction measurement]

[0078] In the present specification, the powder X-ray diffraction measurement can be measured by an X-ray diffraction device. As the X-ray diffraction device, for example, Ultima IV can be used.

[0079] Specifically, the powder of the lithium precursor is filled into a dedicated substrate, and a Cu-Kα ray source is used to measure the powder X-ray diffraction spectrum under the conditions of a diffraction angle of 2θ=10°~90°, an operating voltage of 40 kV, a sampling amplitude of 0.002°, and a scanning speed of 5° / min.

[0080] The powder X-ray diffraction pattern of the lithium-containing precursor of the positive electrode material using Cu-Kα rays shows that the precursor has a layered structure.

[0081] From the obtained X-ray diffraction spectrum, peaks within the range of 2θ=18.6±0.3, 21.2±0.3, 30.5±0.3, 31.7±0.3, 36.4±0.3, 38.0±0.3, 44.1±0.3, 48.4±0.3, 58.3±0.3, 64.2±0.3, and 67.7±0.3 degrees were confirmed.

[0082] In one embodiment, in the powder x-ray diffraction pattern of the positive electrode material lithium-containing precursor using Cu-Kα radiation, the ratio of the half-peak width α of the peak at 18.6±0.3 degrees 2θ to the half-peak width β of the peak at 44.1±0.3 degrees 2θ is 1.1 to 1.4.

[0083] The upper limit value and the lower limit value of the half-peak width ratio (α / β) may be arbitrarily combined.

[0084] For example, the half-width ratio (α / β) is preferably 1.2 or more and 1.3 or less.

[0085] In this embodiment, it is believed that if the ratio (α / β) is within the above-mentioned specific range, when the lithium-containing precursor is fired into the positive electrode material, the particles grow regularly. Therefore, it can be inferred that the positive electrode material prepared by the lithium-containing precursor of the present application can improve the initial charge and discharge efficiency when used in a lithium secondary battery. At the same time, after the lithium-containing precursor that satisfies the above-mentioned specific range is prepared into a positive electrode material, the movement resistance of the lithium ions accompanying charging and discharging is small, and the cycle maintenance rate of the lithium secondary battery can be improved.

[0086] In some embodiments, the half-peak width α ranges from 0.60 to 0.80 degrees, and the half-peak width β ranges from 0.40 to 0.60 degrees. The upper and lower limits of α and β can be arbitrarily combined.

[0087] For example, α is preferably 0.61 to 0.79, more preferably 0.65 to 0.75, and even more preferably 0.68 to 0.73. β is preferably 0.41 to 0.58, more preferably 0.43 to 0.56, and even more preferably 0.45 to 0.55.

[0088] For example, α can be selected as 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80 degrees. β can be selected as 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60 degrees.

[0089] In this embodiment, it is believed that if α and β are in the above-mentioned specific ranges, when the lithium-containing precursor is fired into the positive electrode material, the particles grow regularly. Therefore, it can be inferred that the positive electrode material prepared by the lithium-containing precursor of the present application can improve the initial charge and discharge efficiency when used in a lithium secondary battery. At the same time, after the lithium-containing precursor that satisfies the above-mentioned specific range is prepared into a positive electrode material, the movement resistance of the lithium ions accompanying charging and discharging is small, and the cycle maintenance rate of the lithium secondary battery can be improved.

[0090] In the present embodiment, the half-peak width α of the peak existing in the range of diffraction angle 2θ=18.6±0.3° (hereinafter, sometimes referred to as "peak A") and the half-peak width β of the peak existing in the range of 2θ=44.1±0.3° (hereinafter, sometimes referred to as "peak B") can be calculated by the following method. First, the precursor is subjected to powder X-ray diffraction measurement using Cu-Kα as a radiation source and setting the measurement range of the diffraction angle 2θ to be greater than 10° and less than 90°, and peak A and peak B are determined. Next, the profile of each diffraction peak is approximated by a Gaussian function, and the difference in 2θ between two points where the value of the second differential curve becomes zero is multiplied by 2ln2 (≈1.386) as a coefficient to calculate the half-peak width α and the half-peak width β (for example, refer to "The Reality of Powder X-ray Analysis - An Introduction to the Rietveld Method", 7th edition, June 20, 2006, written by Izumi Nakai and Fujio Izumi).

[0091] In a preferred embodiment, in the powder x-ray diffraction pattern using Cu-Kα radiation, the peak intensity of the peak at 18.6±0.3 degrees 2θ is I a , the peak intensity of the peak at 44.1±0.3 degrees 2θ is I b , I a with I b The peak intensity ratio is greater than or equal to 0.2 and less than 1.

[0092] Peak intensity ratio (I a / I b )The upper and lower limits can be combined arbitrarily.

[0093] For example, the peak intensity ratio (I a / I b ) is preferably from 0.22 to 0.99, more preferably from 0.30 to 0.95, further preferably from 0.7 to 0.9.

[0094] Specifically, I a / I b You can choose 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.

[0095] The peak at 18.6±0.3 degrees 2θ is usually considered to be the (003) peak, and the peak at 44.1±0.3 degrees 2θ is usually considered to be the (104) peak. The ratio of the peak intensities at these two locations can reflect the degree of cation mixing in the material. Generally, the higher the I(003) / I(104) value, the lower the degree of cation mixing in the lattice. Excessive cation mixing will hinder Li + Deintercalation leads to Li +The diffusion coefficient decreases and the electrochemical performance of the material decreases. The I(003) / I(104) value of the positive electrode material is usually significantly higher than 1.2, indicating that it has a lower cation mixing. The peak intensity I of the peak at 18.6±0.3 degrees 2θ of the positive electrode material containing lithium precursor is a The peak intensity I of the peak at 44.1±0.3 degrees 2θ is less than b , therefore, the ratio of the two is less than 1, indicating that the lithium-containing nickel-cobalt-manganese positive electrode precursor has a higher cation mixing than the nickel-cobalt-manganese positive electrode material, and sintering is required to reduce the cation mixing. After the lithium-containing precursor of the present application is used to prepare the positive electrode material, the I(003) / I(104) value of the positive electrode material is usually significantly higher than 1.2. Therefore, it can be inferred that the positive electrode material prepared by the lithium-containing precursor of the present application can improve the initial charge and discharge efficiency when used in a lithium secondary battery. Satisfying the above I a / I b When a lithium-containing precursor within a specific range is prepared into a positive electrode material, cation mixing is reduced and the cycle maintenance rate of a lithium secondary battery can be improved.

[0096] In one embodiment, the half-peak width of the peak at 18.6±0.3 degrees 2θ of the XRD of the positive electrode material containing lithium precursor is 0.60-0.80 degrees, for example, 0.63 degrees, and the half-peak width of the peak at 44.1±0.3 degrees 2θ is 0.40-0.60 degrees, for example, 0.49 degrees. The half-peak width of the peak at 18.6±0.3 degrees 2θ and the peak at 44.1±0.3 degrees 2θ of the XRD spectrum of the positive electrode material containing lithium precursor is small, indicating that the peak shape is good and has good crystallinity, but the half-peak width is greater than the half-peak width of the corresponding nickel-cobalt-manganese positive electrode material, which indicates that the crystallinity of the positive electrode material containing lithium precursor is still not as good as that of the nickel-cobalt-manganese positive electrode material.

[0097] In one embodiment, the ratio of the tap density (TBD) to the bulk density (LBD) of the lithium-containing precursor of the positive electrode material is 2 or more.

[0098] The upper limit and lower limit of the ratio of the tap density (TBD) to the bulk density (LBD) may be arbitrarily combined.

[0099] From the viewpoint of obtaining a lithium secondary battery with a high electrode density, for example, (TBD / LBD) is preferably greater than 2. The value of TBD / LBD has no upper limit, but if the relationship between TBD and LBD becomes unbalanced, the more inhomogeneous particle shape or the fillability of the particles deteriorates, and when the lithium-containing precursor is prepared into a positive electrode material, the electrode density of the lithium secondary battery is further affected.

[0100] The lower limit of TBD / LBD of the lithium-containing precursor is 2, preferably 2.1, more preferably 2.5, further preferably 2.8, and more preferably 3. The upper limit of TBD / LBD of the lithium-containing precursor is not particularly limited, but the upper limit is preferably 8, more preferably 6. For example, the value of TBD / LBD of the lithium-containing precursor may be in the range of 2 to 8, or in the range of 2.3 to 5.1.

[0101] For example, TBD / LBD is 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0102] In the present embodiment, from the viewpoint of obtaining a lithium secondary battery with a high electrode density, the tap density of the lithium-containing precursor is preferably 0.8 g / cm 3 More preferably 1.2 g / cm 3 Above, particularly preferably 1.4 g / cm 3 In addition, from the perspective of increasing the unit loading amount, thereby increasing the output when sintering the positive electrode material and reducing the manufacturing cost of the positive electrode material, 2.5 g / cm 3 Below, more preferably 2.0 g / cm 3 Below, particularly preferably 1.9 g / cm 3 the following.

[0103] The upper and lower limits of the tap density can be arbitrarily combined. For example, the tap density is preferably 1.0 g / cm 3 Above and 2.2g / cm 3 Below, more preferably 1.2 g / cm 3 Above and 2.0g / cm 3 Below, more preferably 1.4 g / cm 3 Above and 1.9g / cm 3 the following.

[0104] In this embodiment, from the viewpoint of obtaining a lithium secondary battery with a high electrode density, the bulk density of the lithium-containing precursor is preferably 0.4 or more, more preferably 0.41 g / cm 3 Above, particularly preferably 0.45 g / cm 3 In addition, from the perspective of increasing the unit loading amount, thereby increasing the yield when sintering the positive electrode material and reducing the manufacturing cost of the positive electrode material, 0.9 g / cm 3 Below, more preferably 0.8 g / cm 3Below, particularly preferably 0.7 g / cm 3 the following.

[0105] The upper and lower limits of the bulk density can be arbitrarily combined. For example, the bulk density is preferably 0.41 g / cm 3 Above 0.88g / cm 3 Below, more preferably 0.45g / cm 3 Above and 0.85g / cm 3 Below, more preferably 0.5 g / cm 3 Above and 0.7g / cm 3 the following.

[0106] The lithium-containing precursor of the positive electrode material disclosed in the present application has a larger loose density and a tap density. When sintered into a positive electrode material, the unit filling amount is increased, thereby increasing the output when sintered into a positive electrode material and reducing the manufacturing cost of the positive electrode material.

[0107] [Determination of tap density]

[0108] Use a 25 mL measuring cylinder to hold 23-25 ​​mL of the lithium-containing precursor sample, weigh the mass of the sample, vibrate at a frequency of 250 times / min with a vibration amplitude of 3 mm, read the volume of the sample after vibrating 3000 times, and calculate the tap density.

[0109] [Determination of bulk density]

[0110] Using the Scott volumetric method, the lithium-containing precursor powder is passed through a series of inclined baffles in the Scott volumetric meter to fill a volume of 25 cm 3 Use a cylindrical cup to weigh the mass of the lithium-containing precursor sample, and calculate the ratio of mass to volume, which is the bulk density.

[0111] In one embodiment, the D90 / D10 value of the positive electrode material lithium-containing precursor determined from a particle size distribution measurement value is 4 or more and 12 or less.

[0112] In the present embodiment, the ratio of the 90% cumulative volume particle size D90 to the 10% cumulative volume particle size D10 (D 90 / D10) of the lithium-containing precursor is 4.0 or more. In the present embodiment, D 90 / D 10 is preferably 4.1 or more, more preferably 4.5 or more, and particularly preferably 5 or more. The upper limit of D 90 / D 10 is not particularly limited, and if an example is given, it can be 12 or less, preferably 8 or less.

[0113] The upper limit and lower limit of D 90 / D 10 may be arbitrarily combined. For example, D 90 / D 10 is 4.0 to 12.0, preferably 4.0 to 10.0, more preferably 4.5 to 9.0, and particularly preferably 5.0 to 8.0.

[0114] [Cumulative volume particle size was measured by laser diffraction scattering method]

[0115] Use laser particle size analyzer (instrument manufacturer: Malvern, model: Mastersizer 3000) to test. Add a small amount of sample to 20 mL of 10% sodium hexametaphosphate solution, perform external ultrasound for 2-5 minutes, add to the particle size tester for testing, and obtain the cumulative volume particle size distribution curve.

[0116] Then, in the obtained cumulative particle size distribution curve, the value of the particle size observed from the tiny particle side at the cumulative 10% is the 10% cumulative volume particle size D10 (μm), the value of the particle size observed from the tiny particle side at the cumulative 90% is the 90% cumulative volume particle size D90 (μm), and the value of the particle size observed from the tiny particle side at the cumulative 50% is the 50% cumulative volume particle size D50 (μm).

[0117] In some embodiments, the D90 is 5 to 38 μm, and the D10 is 0.5 to 7.6 μm.

[0118] Among them, the 90% cumulative volume particle size D90 of the lithium-containing precursor is preferably 5 to 38 μm, more preferably 5.5-35 μm, and further preferably 6-30 μm. When the 90% cumulative volume particle size D90 of the lithium-containing precursor is within the range of 5-38 μm, even if the lithium secondary battery is repeatedly charged and discharged, the positive electrode material prepared by the lithium-containing precursor is not prone to cracking of the crystal interface between particles accompanied by the insertion and deinsertion reaction of lithium ions, thereby improving the cycle maintenance rate of the lithium secondary battery.

[0119] For example, D90 can be selected as 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm.

[0120] D10 can be selected as 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 10μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, and 7.5μm.

[0121] Among them, the 10% cumulative volume particle size D10 of the lithium-containing precursor is preferably 0.5-7.6μm, more preferably 0.6-7.4μm, and further preferably 0.7-6.8μm. When the 10% cumulative volume particle size D10 of the lithium-containing precursor is within the range of 0.5-7.6μm, even if the lithium secondary battery is repeatedly charged and discharged, the positive electrode material prepared by the lithium-containing precursor is not prone to cracking of the crystal interface between particles accompanied by the insertion and deinsertion reaction of lithium ions, thereby improving the cycle maintenance rate of the lithium secondary battery.

[0122] In some embodiments, the D90 / D50 value of the positive electrode material lithium-containing precursor determined from the particle size distribution measurement value is 1.5-5.

[0123] In the present embodiment, the ratio of the 90% cumulative volume particle size D 90 to the 50% cumulative volume particle size D50 (D 90 / D50) of the lithium-containing precursor is 1.5 or more. In the present embodiment, D 90 / D 50 is preferably 1.6 or more, more preferably 2 or more, and particularly preferably 2.1 or more. The upper limit of D 90 / D50 is not particularly limited, and if an example is given, it can be 5 or less, preferably 4.5 or less.

[0124] The upper limit and lower limit of D 90 / D 50 may be arbitrarily combined. For example, D 90 / D 50 is 1.5 to 5.0, preferably 1.6 to 4.8, more preferably 2 to 4.5, and particularly preferably 2.1 to 4.0.

[0125] When the lithium-containing precursor having a D 90 / D 50 value within the above specific range is prepared into a positive electrode material, irreversible reactions can be easily suppressed, thereby improving the cycle retention rate of the lithium secondary battery.

[0126] Among them, the 50% cumulative volume particle size D50 of the lithium-containing precursor is preferably 1.0-12μm, more preferably 1.2-11μm, and further preferably 1.5-10μm. When the 10% cumulative volume particle size D50 of the lithium-containing precursor is within the range of 1.0-12μm, even if the lithium secondary battery is repeatedly charged and discharged, the positive electrode material prepared by the lithium-containing precursor is not prone to cracking of the crystal interface between particles accompanied by the insertion and deinsertion reaction of lithium ions, thereby improving the cycle maintenance rate of the lithium secondary battery.

[0127] For example, D 50 can be selected as 1 μm, 1.2 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, or 12 μm.

[0128] In some embodiments, the ratio of the specific surface area of ​​the lithium-containing precursor of the positive electrode material to D50 is 3×10 6 ~15×106 m / g.

[0129] In the lithium-containing precursor of this embodiment, the specific surface area is S, and the ratio of the specific surface area to the 50% cumulative volume particle size D50 is S / D50, and S / D50 is 3×10 6 ~15×10 6 m / g, preferably 3.5×10 6 ~12×10 6 m / g, more preferably 3.8×10 6 ~10×10 6 m / g, more preferably 4.0×10 6 ~8×10 6 m / g, particularly preferably 5.0×10 6 m / g or more and less than 7.8×10 6 m / g. If S / D50 is 3×10 6 m / g or more, it can be said that the lithium-containing precursor is not excessively crystallized. 6 m / g or less, the primary particles contained in the lithium-containing precursor aggregate at an appropriate density.

[0130] If S / D50 is 3×10 6 ~15×10 6 m / g of lithium-containing precursor to produce the positive electrode material, a positive electrode material with a large area involved in the insertion and extraction of lithium ions and high discharge rate characteristics of the lithium secondary battery can be obtained.

[0131] For example, S / D50 can be selected as 3×10 6 m / g, 4×10 6 m / g, 5×10 6 m / g, 6×10 6 m / g, 7×10 6 m / g, 8×10 6 m / g, 9×10 6 m / g, 10×10 6 m / g, 11×10 6 m / g, 12×10 6 m / g, 13×10 6 m / g, 14×10 6 m / g, 15×10 6 m / g.

[0132] In some embodiments, the BET specific surface area of ​​the positive electrode material containing lithium precursor is 2 to 20 m 2 / g. The upper limit value and the lower limit value of the BET specific surface area can be arbitrarily combined.

[0133] In the lithium-containing precursor of this embodiment, the BET specific surface area of ​​the lithium-containing precursor is preferably 2 to 20 m 2 / g, more preferably 3 to 18 m 2 / g, more preferably 4 to 15m 2 / g. If the BET specific surface area of ​​the precursor is 2 to 20 m 2 / g, the primary particles contained in the lithium-containing precursor aggregate at an appropriate density. Therefore, if such a lithium-containing precursor is used to produce a positive electrode material, a positive electrode material with high discharge rate characteristics of a lithium secondary battery can be obtained.

[0134] For example, the BET surface area of ​​the lithium-containing precursor of the positive electrode material is 2 m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g.

[0135] [Measurement of specific surface area]

[0136] 2.5 g of lithium-containing precursor sample was heated in vacuum at 200°C for 1 h and tested using a BET surface area tester. Instrument manufacturer: American Micrometer, instrument model: tristarⅡ3030.

[0137] In some embodiments, the positive electrode material contains less than 500 ppm of calcium ions in the lithium precursor.

[0138] In the lithium-containing precursor of the present embodiment, the calcium ion in the lithium-containing precursor is more preferably less than 400 ppm / g, and more preferably less than 300 ppm. In general, the lower limit of the calcium ion in the lithium-containing precursor is not limited. Considering the production cost of impurities removal, the content of calcium ions in the lithium-containing precursor can be more than 20 ppm. More preferably, the calcium ion in the lithium-containing precursor is more than 100 ppm.

[0139] The upper limit and lower limit of calcium ions in the lithium-containing precursor can be combined arbitrarily. For example, the content of calcium ions in the lithium-containing precursor is more than 20ppm and less than 480ppm, preferably more than 50ppm and less than 400ppm, and more preferably more than 100ppm and less than 300ppm. Compared with the precursor in the prior art, the impurity content of impurity calcium in the embodiment of the present application may be higher, but calcium generally has little effect on the performance of the product, and if this impurity is to be removed, then an additional impurity removal process is required, and even new additives need to be introduced, which undoubtedly increases the cost. After the lithium-containing precursor with a content of calcium ions in the lithium-containing precursor being the above-mentioned specific range is prepared into a positive electrode material, the discharge rate characteristics of a high lithium secondary battery can be maintained while reducing costs.

[0140] In some embodiments, the content of magnesium ions in the lithium-containing precursor of the positive electrode material is less than 500 ppm.

[0141] In the lithium-containing precursor of the present embodiment, the magnesium ions in the lithium-containing precursor are more preferably less than 400 ppm / g, and more preferably less than 300 ppm. In general, the lower limit of the magnesium ions in the lithium-containing precursor is not limited. Considering the production cost of impurities removal, the lithium content of the magnesium ions in the lithium-containing precursor can be more than 20 ppm. More preferably, the magnesium ions in the lithium-containing precursor are more than 100 ppm.

[0142] The upper limit and lower limit of magnesium ions in the lithium-containing precursor can be arbitrarily combined. For example, the content of magnesium ions in the lithium-containing precursor is more than 20ppm and less than 480ppm, preferably more than 50ppm and less than 400ppm, and more preferably more than 100ppm and less than 300ppm. Compared with the precursor in the prior art, the impurity content of our impurity magnesium may be higher, and if this impurity is to be removed, then an additional impurity removal process is required, and even new additives need to be introduced, which undoubtedly increases the cost. After the lithium-containing precursor with a content of magnesium ions in the lithium-containing precursor being within the above-mentioned specific range is prepared into a positive electrode material, the discharge rate characteristics of a high lithium secondary battery can be maintained while reducing costs.

[0143] In some embodiments, the content of sulfate in the lithium-containing precursor of the positive electrode material is less than 50 ppm.

[0144] In the lithium-containing precursor of the present embodiment, the sulfate content in the lithium-containing precursor is 50 ppm or less, and more preferably 45 ppm or less. Generally, there is no limit on the lower limit of the sulfate content in the lithium-containing precursor. Considering the production cost of impurity removal, the sulfate content in the lithium-containing precursor can be 5 ppm or more.

[0145] The upper limit and lower limit of the sulfate content in the lithium-containing precursor can be arbitrarily combined. For example, the sulfate content in the lithium-containing precursor is 1 ppm to 48 ppm, preferably 2 ppm to 45 ppm, and more preferably 5 ppm to 40 ppm.

[0146] At present, the ternary precursor uses sulfate as the main metal raw material, adopts the coprecipitation method, and nickel salt, cobalt salt, and manganese salt are prepared into a salt solution in a certain proportion. Under the action of a precipitant and a complexing agent, a metal hydroxide system or a metal carbonate system precursor is formed, and a qualified product is obtained by washing, filtering, drying and other processes. During the coprecipitation reaction, sulfate is mainly present in the mother liquor in the form of sodium sulfate. A large amount of sulfate will be adsorbed on the surface or inside of the crystal, and it is necessary to wash with pure water to reduce the sulfur content. Part of the sulfate remaining inside the crystal will become an impurity in the positive electrode material, affecting the capacity and cycle performance of the positive electrode material, causing the overall performance of the battery to decline. The lithium-containing precursor of the present application has extremely low sulfate impurities, which will not affect the capacity and cycle performance of the positive electrode material, and improve the overall performance of the battery.

[0147] In some embodiments, the sodium ion content in the lithium-containing precursor of the positive electrode material is below 50 ppm.

[0148] In the lithium-containing precursor of the present embodiment, the sodium ion content in the lithium-containing precursor is 50 ppm or less, more preferably 45 ppm or less, more preferably 30 ppm or less, and even more preferably 10 ppm or less.

[0149] The lithium-containing precursor of the present application has extremely low sodium ion impurities, which prevents sodium ions from affecting the capacity and cycle performance of the positive electrode material, thereby improving the overall performance of the battery.

[0150] In some embodiments, the contents of hydrochloride, phosphate and oxalate in the lithium-containing precursor of the positive electrode material are each below 100 ppm.

[0151] In the lithium-containing precursor of the present embodiment, the contents of hydrochloride, phosphate and oxalate in the lithium-containing precursor are each 100 ppm or less, more preferably 80 ppm or less, more preferably 60 ppm or less, and even more preferably 50 ppm or less.

[0152] The lithium-containing precursor of the present application has extremely low hydrochloride, phosphate, and oxalate, which prevents these impurity ions from affecting the capacity and cycle performance of the positive electrode material, thereby improving the overall performance of the battery.

[0153] [Determination of metal ion content]

[0154] Thermo Fisher ICP-OES was used for testing (instrument manufacturer: Thermo Fisher, model: ICAPPROX).

[0155] Impurity test: Add a small amount of lithium-containing precursor sample into a 100mL beaker, add 6mL hydrochloric acid and 2mL nitric acid for digestion, filter after cooling (if necessary), and dilute to a 100mL volumetric flask to test the metal ion content in the lithium-containing precursor.

[0156] [Determination of chloride ion content]

[0157] Weigh 1g of lithium-containing precursor sample, wet the sample with water, add concentrated nitric acid and hydrogen peroxide, and dissolve the sample under stirring and boiling conditions. The Cl in the sample - With H + Generate volatile HCl, use a sealed container and a catheter to absorb the volatilized HCl with ultrapure water, and use a potentiometric titrator (silver nitrate standard titration solution) to test the Cl absorbed in the ultrapure water. - content.

[0158] [Determination of carbon or sulfur composition]

[0159] Use Wanlianda CS-901B high-frequency infrared carbon and sulfur instrument to test carbon or sulfur (instrument manufacturer: Wanlianda, model: CS-901B6). Impurity test: burn the ceramic crucible at 900℃ for 4h and then cool it to room temperature. First test 3 sets of standard samples for calibration, then weigh 0.4±0.01g of iron flux in the crucible, return to zero, and then weigh a certain amount of lithium-containing precursor sample, add a spoonful of tungsten particles, test the lithium-containing precursor sample on the machine, click analysis, and output the data.

[0160] In some embodiments, the crystal structure of the lithium-containing precursor of the positive electrode material is a layered structure.

[0161] After the positive electrode material is formed using the lithium-containing precursor of the present application, the hexagonal layered structure is a two-dimensional structure, which is conducive to the deintercalation of lithium ions, thereby increasing the specific capacity of the positive electrode material.

[0162] In some embodiments, the crystal form of the lithium-containing precursor of the positive electrode material is one or more of spinel, cubic, and octahedral.

[0163] The cubic structure is conducive to improving the uniformity of lithium-containing precursor materials, reducing agglomeration, and improving product stability, so that the cycle performance and rate performance are higher. The lithium-containing precursor with an octahedral structure has a higher active specific surface area, which is also conducive to lithium ion deintercalation, and the precursor particle size is highly uniform, which is conducive to improving the film density, flatness and uniformity of the positive electrode sheet, thereby improving the cycle stability of the battery. The spinel type is a three-dimensional cubic structure, and the crystal itself has a high structural stability, which is conducive to improving the cycle stability and rate performance of the positive electrode material.

[0164] In some embodiments, the positive electrode material contains a lithium precursor with a charge and discharge voltage of 3.0 to 4.4 V and a 0.1C first discharge capacity of less than 130 mAh / g.

[0165] Compared with traditional precursors, the lithium-containing precursor in the embodiment of the present application already has lithium, so lithium can be deintercalated for charging and discharging, and therefore, the lithium-containing precursor in the present application has a higher initial efficiency than the traditional precursor. However, since the crystal structure of the lithium-containing precursor in the embodiment of the present application has not yet grown completely, the lithium-containing precursor in the embodiment of the present application has a lower initial efficiency than the positive electrode material and cannot be directly used as the positive electrode material of a lithium secondary battery.

[0166] In the lithium-containing precursor of the present embodiment, the lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of 130 mAh / g or less. It is further preferred that the lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of 120 mAh / g or less. It is further preferred that the lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of 100 mAh / g or less, and further that the lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of 70 mAh / g or less. The lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of more than 10 mAh / g, and further that the lithium-containing precursor has a charge and discharge voltage of 3.0 to 4.4 v, and a 0.1C first discharge capacity of more than 20 mAh / g.

[0167] The upper and lower limits of the capacity of the lithium-containing precursor at a charge and discharge voltage of 3.0 to 4.4 v and a 0.1C first discharge can be arbitrarily combined. For example, the capacity of the lithium-containing precursor at a charge and discharge voltage of 3.0 to 4.4 v and a 0.1C first discharge is below 120 mAh / g and above 5 mAh / g, the capacity of the lithium-containing precursor at a charge and discharge voltage of 3.0 to 4.4 v and a 0.1C first discharge is below 110 mAh / g and above 10 mAh / g, and the capacity of the lithium-containing precursor at a charge and discharge voltage of 3.0 to 4.4 v and a 0.1C first discharge is below 68 mAh / g and above 20 mAh / g.

[0168] In the embodiment of the present application, after the positive electrode material is prepared from a lithium-containing precursor with a charge and discharge voltage of 3.0 to 4.4V and a capacitance at 0.1C first discharge within the above-mentioned specific range, the capacitance at a charge and discharge voltage of 3.0 to 4.4V and a capacitance at 0.1C first discharge can be significantly improved, so that the discharge rate characteristics of the lithium secondary battery are good while reducing costs.

[0169] <Power-off test>

[0170] [Charge and discharge test]

[0171] A half-cell was fabricated using the lithium-containing precursor described above, and after initial charge and discharge, a discharge rate test and a cycle test were performed to evaluate the discharge rate characteristics and the cycle characteristics.

[0172] The ambient temperature of the battery is controlled at 25.0℃±0.2℃. The first charge and discharge and first efficiency test steps of 4.4V 0.1C are divided into 4 steps:

[0173] 1. Let the prepared half-cell stand for ≥12h;

[0174] 2. Charge at a rate of 0.1C, and the end condition is voltage ≥ 4.4V;

[0175] 3. Constant voltage charging, the end condition is current ≤ 50μA;

[0176] 4. Discharge rate is 0.1C, and the end condition is voltage ≤ 3V.

[0177] First efficiency = first discharge capacity (mAh / g) ÷ first charge capacity (mAh / g) × 100.

[0178] [Measurement method of cycle maintenance rate]

[0179] [Cycle test]

[0180] Using coin-type batteries, follow the cycle test conditions shown below.

[0181] Test temperature: 25℃, charging and discharging steps are as follows:

[0182] 1. Stand still, the end condition is time ≥ 12h;

[0183] 2. Charge at a rate of 0.1C, and the end condition is voltage ≥ 4.4V;

[0184] 3. Constant voltage charging, the end condition is current ≤ 50μA;

[0185] 4. Discharge rate is 0.1C, and the end condition is voltage ≤ 3V.

[0186] Steps 1 to 4 are cycled once, and then step 2 to 4 are repeated for 49 times, for a total of 50 cycles. Life evaluation is performed through 50 cycle tests, and the discharge capacity retention rate after 50 cycles is calculated by the following formula. It should be noted that the higher the discharge capacity retention rate after 50 cycles, the better the high voltage cycle characteristics.

[0187] Discharge capacity retention rate after 50 cycles (%) = 50th discharge capacity / 1st discharge capacity × 100. The discharge capacity retention rate after 50 cycles may be described as “cycle retention rate” herein.

[0188] The lithium-containing precursor of the positive electrode material disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no waste water is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with a traditional hydroxide precursor, the content of the main metals of nickel, cobalt and manganese in the oxide precursor is higher. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the loss rate of lithium during sintering of the positive electrode material is reduced, and the yield of the finished product under the same loading amount is improved, thereby increasing the output when sintering into the positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity.

[0189] The second aspect of the present disclosure provides a method for preparing a positive electrode material containing lithium precursor material, according to the positive electrode material and Li a (Ni x Co y Mn 1-x-y ) (1+a) The stoichiometric ratio of the metal elements in the chemical formula, after mixing lithium nitrate, nickel nitrate solution, cobalt nitrate solution, and manganese nitrate solution, the concentration of lithium salt, nickel salt, cobalt salt, and manganese salt in the mixed solution is regulated by concentration treatment; the mixed solution is subjected to atomization and roasting treatment, and the mixed solution is atomized into fine droplets, and the atomized droplets are directly roasted, so that the metal cations such as lithium, nickel, cobalt, and manganese in the droplets react rapidly in a high temperature environment to form an oxide-containing lithium precursor, and the anions in the salt solution are converted into gaseous substances such as nitrogen oxides in a high temperature environment to be removed or recovered, thereby obtaining a positive electrode precursor material with high product purity, small particle size, and good uniformity. The preparation method has a simple process flow, few intermediate processes, and the reaction process is easy to flexibly control. The roasting treatment is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also a fast product reaction speed. The actual reaction time of the lithium-containing positive electrode material obtained by atomization and roasting is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high-temperature environment and removed or recovered, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent.

[0190] The method disclosed herein directly prepares a positive electrode precursor material by atomizing and roasting a mixed solution, which is beneficial to improving the structural stability of the precursor material, improving the density of the precursor material, and refining the particle size of the material, thereby further improving the unit loading amount of the precursor material, improving the preparation efficiency of the positive electrode material, and reducing the manufacturing cost. Compared with the traditional method of preparing a ternary hydroxide precursor by coprecipitation method, it not only improves the preparation efficiency of the material, simplifies the process, reduces the discharge of industrial waste such as wastewater, and makes the production process more environmentally friendly and reduces the production cost; and it is more conducive to regulating the crystal structure, particle size, looseness, density and other properties of the precursor material, and overcomes the problems of poor structural stability, low density, and poor controllability of particle size in the existing secondary crystallization-coated ternary hydroxide precursor material.

[0191] In some embodiments, a nitrate solution containing lithium, nickel, cobalt, and manganese is transferred to a mixing tank for mixing to prepare a mixed solution containing lithium, nickel, cobalt, and manganese ions, wherein the mixing tank is made of an acid-resistant material with a certain strength.

[0192] In some embodiments, after mixing the lithium salt solution, the nickel salt solution, the cobalt salt solution, and the manganese salt solution, a concentration treatment is performed to control the total concentration of lithium salt, nickel salt, cobalt salt, and manganese salt in the obtained mixed solution to be 50 to 300 g / L. Such a metal salt concentration is conducive to atomization crystallization granulation. If the total concentration of metal salts in the mixed solution is lower than 50 g / L, the metal salt content in the droplets after atomization will be too low, which is not conducive to the full reaction and crystallization granulation of the metal salts in the droplets during the roasting process, and the obtained product is less, which is not conducive to the enrichment of the precursor; if the total concentration of metal salts in the mixed solution is higher than 300 g / L, the metal salt content in the droplets after atomization is too high, which is not conducive to the crystallization and granulation of the metal salt components during the roasting process, and the particle size is too large, which is not conducive to the preparation of single crystal materials, nor is it conducive to the regulation of the material crystal form, thereby reducing the stability of the positive electrode precursor. In some specific embodiments, in the mixed solution, the total concentration of lithium salt, nickel salt, cobalt salt and manganese salt is 50 g / L, 60 g / L, 80 g / L, 120 g / L, 160 g / L, 200 g / L, 220 g / L, 260 g / L, 300 g / L, etc.

[0193] In some embodiments, the step of atomizing and roasting the mixed solution includes: spray pyrolysis in a spray dryer, wherein the air-to-coal ratio (ratio of air and natural gas flow) of the roasting furnace burner is less than or equal to 10, for example, 8.5:1 to 10:1; atomization parameters: compressed air pressure ≥ 0.2MPA, for example, 0.2-0.5MPA; compressed air and liquid flow volume ratio is 50-300:1, and the pyrolysis temperature is controlled to be 400-1000°C, for example, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000°C. In some embodiments, the pyrolysis temperature is controlled to be 500-680°C. The lower the pyrolysis temperature, the higher the lithium carbonate content in the precursor. The higher the pyrolysis temperature, the higher the energy consumption. The nitrate solution is atomized in a spray dryer to form droplets. The droplets quickly lose water under the action of hot air, and the nitrate undergoes pyrolysis and is converted into oxides. The nanoparticles in the droplets agglomerate to form large agglomerates, which are the precursor powders. During the spray pyrolysis process, the nano-scale primary particles aggregate into micron-scale agglomerates, which is beneficial to increase the compaction density of the nickel cobalt manganese oxide positive electrode material produced after calcination, thereby increasing the volume energy density of the nickel cobalt manganese oxide positive electrode material as a lithium ion battery electrode material. By adjusting the burner air-to-coal ratio, compressed air pressure, and compressed air and liquid flow volume ratio during the atomization roasting process, the particle size, crystal form and other physical properties of the prepared positive electrode precursor material can be flexibly controlled, which is beneficial to optimize the physical and chemical properties of the positive electrode material.

[0194] In some embodiments, the calcination time is controlled to be 1 to 50 seconds. In this process, a shaped lithium-containing precursor can be prepared in a short time, the preparation time is short, the efficiency is high, and it is conducive to wide application.

[0195] In some embodiments, after the lithium-containing precursor material is prepared, post-processing steps such as grinding or crushing the lithium-containing precursor material are also included. By controlling conditions such as the grinding disc spacing or the crushing gas pressure flow rate, the particle size of the obtained product can be controlled, making the particle size distribution of the positive electrode precursor material more uniform.

[0196] The third aspect of the present disclosure provides a positive electrode material Li (Ni x Co y Mn 1-x-y ) 1+aThe positive electrode material is obtained by sintering the lithium-containing precursor of the positive electrode material, or by mixing the lithium-containing precursor and a supplemented lithium source (a small amount of lithium source is supplemented based on the lithium content in the lithium-containing precursor relative to the lithium content lacking in the positive electrode material) and then sintering. The lithium source can be selected from one or more of lithium carbonate, lithium hydroxide monohydrate, lithium acetate, lithium nitrate, lithium oxalate, lithium acetate, lithium hydroxide, and lithium oxide. For example, the lithium source is selected from lithium carbonate or lithium hydroxide monohydrate.

[0197] In some preferred embodiments, the positive electrode material is obtained by directly sintering the positive electrode precursor material without mixing the positive electrode precursor material with a lithium source.

[0198] Sintering can be carried out in a pure oxygen or air atmosphere, the number of sintering is 1-3 times, and the temperature of the sintering treatment is 400-1050°C. For example, the positive electrode material containing lithium precursor is kept at a first temperature of 400°C-800°C for 1-5 hours, then heated to a second temperature of 800°C-1050°C, and kept at the second temperature for 5-10 hours. Then it is naturally cooled to room temperature. The sintered product is sieved with 300 mesh to obtain the nickel cobalt manganese oxide lithium positive electrode material.

[0199] For example, the positive electrode material that can be provided in the third aspect of the present disclosure is selected from NCM333, NCM523, NCM613, NCM622 and NCM811. Preferably, the positive electrode material is a high-nickel positive electrode material, including but not limited to: LiNi 0.72 Co 0.03 Mn 0.25 O2、LiNi 0.7 Co 0.04 Mn 0.26 O2、LiNi 0.67 Co 0.05 Mn 0.28 O2、LiNi 0.65 Co 0.06 Mn 0.29 O2、LiNi 0.62 Co 0.08 Mn 0.30 O2、LiNi 0.6 Co 0.10 Mn 0.30 O2, etc. These positive electrode materials also have the characteristics of good structural stability, high capacity, and good cycle stability.

[0200] Since the positive electrode material is prepared from the aforementioned lithium-containing precursor, the positive electrode material also inherits the technical effects of the lithium-containing precursor; when the hydroxide precursor is used to prepare the positive electrode material, the positive electrode hydroxide precursor usually needs to be mixed with a lithium source in a solid state and then sintered at a high temperature. However, due to the uneven mixing between solids and the slow diffusion rate of lithium in the solid phase, it may be difficult to evenly distribute lithium. The uneven distribution of lithium will seriously affect the electrochemical properties of the positive electrode material. When the lithium-containing precursor of the present application is used to prepare the positive electrode material, since the lithium-containing precursor itself has lithium, when preparing the positive electrode material, only a small amount of lithium source needs to be added or no lithium source needs to be added to directly sinter it into the positive electrode material, so that the distribution of lithium is more uniform and the electrochemical properties of the positive electrode material are improved. On the other hand, by directly pre-burning lithium into the precursor, the subsequent mixing process of the precursor and the lithium source is reduced, and the production process of the positive electrode material is simplified; relative to the traditional precursor and lithium carbonate sintering process, the decomposition of lithium carbonate into carbon dioxide is reduced, and carbon emissions are reduced; due to the direct pre-burning of lithium into the precursor, the temperature of the lithium-containing precursor of the present application when sintering the positive electrode material is lower than the temperature of the traditional precursor sintering the positive electrode material under the same conditions, so the sintering cost can be reduced. On the other hand, since the positive electrode material precursor supplier and the lithium source supplier are usually independent of each other, the downstream positive electrode material manufacturers need to strictly control the product quality and batch stability of the positive electrode material precursor supplier and the lithium source supplier, which is difficult, which is not conducive to the stability of the preparation of the positive electrode material. The lithium-containing precursor of the present application itself has lithium, therefore, to a certain extent, the raw material supply problem of the positive electrode material manufacturer is solved, and the stability of the preparation of the positive electrode material is improved.

[0201] A fourth aspect of the present application provides a lithium secondary battery, wherein the positive electrode sheet of the lithium secondary battery includes the positive electrode material described above.

[0202] The lithium secondary battery provided in the fourth aspect of the present application, because the positive electrode sheet includes the above-mentioned positive electrode material, the positive electrode material has high gram capacity, cycle stability, structural stability and other characteristics, thereby improving the energy density, cycle stability, and safety performance of the lithium secondary battery.

[0203] In some embodiments, the positive electrode sheet in the lithium secondary battery includes a current collector and an active material layer that are laminated and bonded together, and the active material layer includes a ternary material, a conductive agent, a binder, and the like.

[0204] In some embodiments, the preparation process of making a positive electrode sheet from a positive electrode material is as follows: the positive electrode material, a conductive agent and a binder are mixed to obtain an electrode slurry, the electrode slurry is coated on a current collector, and a positive electrode sheet is prepared through steps such as drying, rolling, and die cutting.

[0205] In some embodiments, the positive electrode current collector includes, but is not limited to, any one of copper foil and aluminum foil.

[0206] In some embodiments, the content of the binder in the electrode slurry is 2wt%-4wt%. The binder may include one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. In some embodiments, the content of the conductive agent in the electrode slurry is 3wt%-5wt%. The conductive agent may include one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.

[0207] The present disclosure does not specifically limit the negative electrode sheet, electrolyte, separator, etc. in the lithium secondary battery, and can be applied to conventional lithium-ion battery systems.

[0208] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the embodiments of the present invention are clearly and completely described below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should belong to the scope of protection of the present invention.

[0209] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0210] Example 1

[0211] Experiment 1.1: Preparation of lithium-containing precursors for cathode materials

[0212] A nitrate solution of nickel, cobalt, manganese and lithium was prepared according to a molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:1.05, wherein the total concentration of nickel nitrate, cobalt nitrate, manganese nitrate and lithium nitrate was 175 g / L;

[0213] The solution is introduced into the synthesis tower, spray pyrolysis is carried out, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as a finished product. The flue gas is drawn from the top by a fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, the nitric acid is recovered by multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0214] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 9:1;

[0215] Atomization parameters: Compressed air pressure: 0.3MPA;

[0216] Compressed air and liquid flow volume ratio: 175:1;

[0217] The temperature of the spray pyrolysis was 550°C, and the calcination time was 10 seconds.

[0218] SEM photos Figures 1 to 3 As shown in the XRD spectrum Figure 4 shown.

[0219] The chemical formula of the lithium-containing precursor is Li 0.60 (Ni 0.60 Co 0.10 Mn 0.30 ) 1.60 (Li2CO3) 0.20 The carbon content in the lithium-containing precursor is 2.34% by weight. The positive electrode material lithium-containing precursor includes a plurality of flaky agglomerates formed by agglomeration of primary particles, the primary particles are 95 nm, the maximum thickness of the agglomerates is 5.3 μm, the maximum length is 18 μm, the maximum width is 14 μm, and the peak intensity of the peak at 18.6±0.3 degrees 2θ in the powder x-ray diffraction spectrum using Cu-Kα rays is I a , the peak intensity of the peak at 44.1±0.3 degrees 2θ is I b , I a with I b The peak intensity ratio is 0.30. The lithium-containing precursor has a layered structure. The tap density of the lithium-containing precursor is 1.55 g / cm 3 , bulk density is 0.51g / cm 3 The ratio of the tap density to the bulk density is 3, the D90 / D10 value of the lithium-containing precursor obtained from the particle size distribution measurement value is 7, the D50 of the lithium-containing precursor obtained from the particle size distribution measurement value is 3.1 μm, and the BET specific surface area is 7.5 m 2 / g. The content of magnesium ions is 380ppm, the content of calcium ions is 350ppm, and the content of sulfate in the lithium-containing precursor is 45ppm.

[0220] Experiment 1.2: Preparation of positive electrode materials

[0221] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 1.1 was heated to 600℃ at a rate of 5℃ / min for 5 hours, then heated to 950℃ at a rate of 5℃ / min for 10 hours, and cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material. The SEM photo of the positive electrode material is as follows Figure 5 As shown in the XRD spectrum Figure 6 shown.

[0222] Experiment 1.3: Preparation of Lithium-ion Batteries

[0223] The steps for preparing lithium-ion batteries include:

[0224] Preparation of positive electrode sheet: According to the lithium precursor in Experiment 1.1 or the positive electrode material in Experiment 1.2, the weight ratio of conductive agent (acetylene black): binder (PVDF) is 85%: 10%: 5%, weighed and mixed and ground. Then, N-methylpyrrolidone (NMP) solvent is added to prepare a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the aluminum foil with a scraper, and dried to obtain a positive electrode sheet that can be directly assembled into the battery.

[0225] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0226] In experiment 1.1, the positive electrode material containing lithium precursor has a first discharge capacity of 67mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, while in experiment 1.2, the positive electrode material has a first discharge capacity of 194.5mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, with an initial coulombic efficiency of 91% and a 50-cycle discharge capacity retention rate of 94.2%.

[0227] Example 2

[0228] Experiment 2.1: Preparation of lithium-containing precursors for cathode materials

[0229] A nitrate solution of nickel, cobalt, manganese and lithium was prepared according to a molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:1.05, wherein the total concentration of nickel nitrate, cobalt nitrate, manganese nitrate and lithium nitrate was 175 g / L;

[0230] The solution is introduced into the synthesis tower, spray pyrolysis is carried out, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as a finished product. The flue gas is drawn from the top by a fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, the nitric acid is recovered by multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0231] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 9:1;

[0232] Atomization parameters: Compressed air pressure: 0.3MPA;

[0233] Compressed air and liquid flow volume ratio: 175:1;

[0234] The temperature of the spray pyrolysis was 600° C., and the calcination time was 10 seconds.

[0235] SEM photos Figures 1 to 3 As shown in the XRD spectrum Figure 4 shown.

[0236] The chemical formula of the lithium-containing precursor is Li 0.72 (Ni 0.60 Co 0.10 Mn 0.30 ) 1.72 (Li2CO3) 0.14 The carbon content in the lithium-containing precursor is 1.67% by weight. The positive electrode material lithium-containing precursor includes a plurality of flaky agglomerates formed by agglomeration of primary particles, the primary particles are 90 nm, the maximum thickness of the agglomerates is 5.8 μm, the maximum length is 16 μm, the maximum width is 15 μm, and the peak intensity of the peak at 18.6±0.3 degrees 2θ in the powder x-ray diffraction spectrum using Cu-Kα rays is I a , the peak intensity of the peak at 44.1±0.3 degrees 2θ is I b , I a with I b The peak intensity ratio is 0.35. The lithium-containing precursor has a layered structure. The tap density of the lithium-containing precursor is 1.59 g / cm 3 , bulk density is 0.54g / cm 3 The ratio of the tap density to the bulk density is 3, the D90 / D10 value of the lithium-containing precursor obtained from the particle size distribution measurement value is 6.5, the D50 of the lithium-containing precursor obtained from the particle size distribution measurement value is 2.9 μm, and the BET specific surface area is 7.9 m 2 / g. The content of magnesium ions is 370ppm, the content of calcium ions is 390ppm, and the content of sulfate in the lithium-containing precursor is 39ppm.

[0237] Experiment 2.2: Preparation of positive electrode materials

[0238] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 2.1 was heated to 600℃ at a rate of 5℃ / min for 5 hours, then heated to 950℃ at a rate of 5℃ / min for 10 hours, and cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material.

[0239] Experiment 2.3: Preparation of Lithium-ion Batteries

[0240] The steps for preparing lithium-ion batteries include:

[0241] Preparation of positive electrode sheet: According to the lithium-containing precursor in Experiment 2.1 or the positive electrode material in Experiment 2.2, the weight ratio of the conductive agent (acetylene black): the binder (PVDF) is 85%: 10%: 5%, weighed and mixed and ground. Then, N-methylpyrrolidone (NMP) solvent is added to prepare a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the aluminum foil with a scraper, and dried to obtain a positive electrode sheet that can be directly assembled into the battery.

[0242] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0243] In Experiment 2.1, the positive electrode material containing lithium precursor has a first discharge capacity of 70mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, while in Experiment 2.2, the positive electrode material has a first discharge capacity of 194.7mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, a first coulombic efficiency of 90.2%, and a 50-cycle discharge capacity retention rate of 94.3%.

[0244] Example 3

[0245] Experiment 3.1: Preparation of lithium-containing precursors for cathode materials

[0246] A nitrate solution of nickel, cobalt, manganese and lithium was prepared according to the molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:0.83, wherein the total concentration of nickel nitrate, cobalt nitrate, manganese nitrate and lithium nitrate was 171 g / L.

[0247] The solution is introduced into the synthesis tower, spray pyrolysis is carried out, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as a finished product. The flue gas is drawn from the top by a fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, the nitric acid is recovered by multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0248] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 9:1;

[0249] Atomization parameters: Compressed air pressure: 0.3MPA;

[0250] Compressed air and liquid flow volume ratio: 175:1;

[0251] The temperature of the spray pyrolysis was 600° C., and the calcination time was 10 seconds.

[0252] SEM photos Figures 1 to 3As shown in the XRD spectrum Figure 4 shown.

[0253] The chemical formula of the lithium-containing precursor is Li 0.72 (Ni 0.60 Co 0.10 Mn 0.30 ) 1.72 (Li2CO3) 0.05 The carbon content in the lithium-containing precursor is 0.6% by weight. The positive electrode material lithium-containing precursor includes a plurality of flaky agglomerates formed by agglomeration of primary particles, the primary particles are 85 nm, the maximum thickness of the agglomerates is 5.5 μm, the maximum length is 16 μm, the maximum width is 15 μm, and the peak intensity of the peak at 18.6±0.3 degrees 2θ in the powder x-ray diffraction spectrum using Cu-Kα rays is I a , the peak intensity of the peak at 44.1±0.3 degrees 2θ is I b , I a with I b The peak intensity ratio is 0.38. The lithium-containing precursor has a layered structure. The tap density of the lithium-containing precursor is 1.64g / cm 3 , bulk density is 0.55g / cm 3 The ratio of the tap density to the bulk density is 3, the D90 / D10 value of the lithium-containing precursor obtained from the particle size distribution measurement value is 6.8, the D50 of the lithium-containing precursor obtained from the particle size distribution measurement value is 2.6 μm, and the BET specific surface area is 8.3 m 2 / g. The content of magnesium ions is 390ppm, the content of calcium ions is 370ppm, and the content of sulfate in the lithium-containing precursor is 42ppm.

[0254] Experiment 3.2: Preparation of positive electrode materials

[0255] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 3.1 and an appropriate amount of lithium carbonate were mixed and heated to 600°C at a rate of 5°C / min for 5 hours, then heated to 950°C at a rate of 5°C / min for 10 hours and cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material.

[0256] Experiment 3.3: Preparation of Lithium-ion Batteries

[0257] The steps for preparing lithium-ion batteries include:

[0258] Preparation of positive electrode sheet: According to the lithium precursor in Experiment 3.1 or the positive electrode material in Experiment 3.2, the weight ratio of conductive agent (acetylene black): binder (PVDF) is 85%: 10%: 5%, weighed and mixed and ground. Then, N-methylpyrrolidone (NMP) solvent is added to prepare a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the aluminum foil with a scraper, and dried to obtain a positive electrode sheet that can be directly assembled into the battery.

[0259] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0260] In Experiment 3.1, the positive electrode material containing lithium precursor has a first discharge capacity of 69mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, while in Experiment 3.2, the positive electrode material has a first discharge capacity of 194.5mAh / g at a charge and discharge voltage of 3.0 to 4.4V and 0.1C, a first coulombic efficiency of 92.3%, and a 50-cycle discharge capacity retention rate of 94.5%.

[0261] Comparative Example 1

[0262] Experiment 4.1: Preparation of cathode material precursor

[0263] A positive electrode material precursor, the preparation of which comprises the following steps:

[0264] According to Ni 0.60 Co 0.10 Mn 0.30 The stoichiometric ratio of the metal elements in the (OH)2 chemical formula is obtained by mixing nickel chloride solution, cobalt chloride solution and manganese chloride solution; then adding ammonia water and NaOH solution according to the molar ratio of ammonia to nickel: 0.5:1, and the molar ratio of alkali to nickel: 2:1, adding ammonia water and sodium hydroxide, controlling the reaction temperature to 55°C and the pH value to 12.0. After the reaction, Ni 0.60 Co 0.10 Mn 0.30 (OH)2 precursor.

[0265] Ni 0.60 Co 0.10 Mn 0.30 The (OH)2 precursor is spherical or quasi-spherical, Ni 0.60 Co 0.10 Mn 0.30 The tap density of the (OH)2 precursor is 1.83 g / cm 3 , Ni 0.60 Co 0.10 Mn 0.30The D50 of the (OH)2 precursor obtained from the particle size distribution measurement is 15 μm, and the BET specific surface area is 15 m 2 / g.

[0266] Experiment 4.2: Preparation of positive electrode materials

[0267] From Experiment 4.1, Ni 0.60 Co 0.10 Mn 0.30 The (OH)2 precursor is mixed with lithium carbonate solid, Ni 0.60 Co 0.10 Mn 0.30 After the (OH)2 precursor is mixed with lithium carbonate solid, it is sintered at least twice to obtain LiNi 0.6 Co 0.1 Mn 0.3 O2 positive electrode material. The difference from Examples 1, 2, and 3 is that the Ni 0.60 Co 0.10 Mn 0.30 The (OH)2 precursor must be mixed with a lithium source to form a positive electrode material. Secondly, when the lithium-containing precursors of Examples 1, 2, and 3 are sintered into positive electrode materials, only one sintering is required to form the positive electrode material, while the Ni 0.60 Co 0.10 Mn 0.30 When the (OH)2 precursor is sintered into the positive electrode material, it must be sintered more than twice to form the positive electrode material.

[0268] Experiment 4.3: Preparation of Lithium-ion Batteries

[0269] The steps for preparing lithium-ion batteries include:

[0270] Positive electrode preparation: According to the Ni in Experiment 4.1 0.60 Co 0.10 Mn 0.30 (OH)2 precursor or experiment 4.2 positive electrode material: conductive agent (acetylene black): binder (PVDF) weight ratio of 85%: 10%: 5%, weigh and mix and grind. Then, add N-methylpyrrolidone (NMP) solvent to prepare a uniform positive electrode slurry. Use a scraper to evenly apply the positive electrode slurry on the aluminum foil, and dry it to obtain a positive electrode sheet that can be directly assembled into the battery.

[0271] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0272] In experiment 4.2, the first discharge capacity of the positive electrode material at a charge and discharge voltage of 3.0 to 4.4 V, a temperature of 25°C, and a 0.1C discharge rate was 194.5 mAh / g, the first coulombic efficiency was 90.1%, and the 50-week discharge capacity retention rate was 94.2%.

[0273] By comparing Examples 1, 2, and 3 with the comparative example, it can be seen that the lithium-containing precursor of the positive electrode material disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no wastewater is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with the traditional hydroxide precursor, the content of the main metals of nickel, cobalt, and manganese in the oxide precursor is higher. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the loss rate of lithium during sintering of the positive electrode material is reduced, and the yield of the finished product under the same loading amount is increased, thereby increasing the output when sintering into the positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity. The lithium-containing precursor in this application is formed by atomization roasting. Compared with the hydroxide precursor prepared by the coprecipitation method, the process of this application is simple, the intermediate process is small, the reaction process is easy to flexibly control, and the roasting process is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also the product reaction speed is fast. The actual reaction time of obtaining the lithium-containing precursor material by atomization roasting is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high temperature environment to be removed or recycled, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent. At the same time, the lithium-containing precursor material product prepared by this method has a better structural stability of the material itself than the traditional coprecipitation method. When the hydroxide precursor prepares the positive electrode material, the positive electrode hydroxide precursor usually needs to be mixed with a lithium source for solid mixing and then sintered at high temperature. However, due to the uneven mixing between solids and the slow diffusion rate of lithium in the solid phase, it may be difficult to make lithium uniformly distributed, and the uneven distribution of lithium will seriously affect the electrochemical properties of the positive electrode material. When the lithium-containing precursor of the present application is used to prepare the positive electrode material, since the lithium-containing precursor itself has lithium, when preparing the positive electrode material, only a small amount of lithium source needs to be added or no lithium source needs to be added to directly sinter the positive electrode material, so that the distribution of lithium is more uniform and the electrochemical performance of the positive electrode material is improved. On the other hand, by directly pre-burning lithium into the precursor, the subsequent mixing process of the precursor and the lithium source is reduced, and the production process of the positive electrode material is simplified; compared with the traditional precursor and lithium carbonate sintering process, the decomposition of lithium carbonate into carbon dioxide is reduced, and carbon emissions are reduced; because lithium is directly pre-burned into the precursor, the temperature of the lithium-containing precursor of the present application when sintering the positive electrode material is lower than the temperature of the traditional precursor sintering the positive electrode material under the same conditions, so the sintering cost can be reduced. On the other hand, since the suppliers of positive electrode material precursors and lithium source suppliers are usually independent of each other, it is difficult for downstream positive electrode material manufacturers to strictly control the product quality and batch stability of positive electrode material precursor suppliers and lithium source suppliers, which is not conducive to the stability of positive electrode material preparation. The lithium-containing precursor of the present application itself contains lithium, therefore, it solves the raw material supply problem of positive electrode material manufacturers to a certain extent and improves the stability of positive electrode material preparation.

[0274] The present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0275] In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other to obtain new embodiments. The protection scope of the present invention is not limited to the above-mentioned embodiments, and the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A lithium-containing precursor of a positive electrode material, characterized in that: It satisfies the chemical formula Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , where a is 0.10 to 1.08; 0<x<1, 0<y <1, and x+y<1; z is greater than 0 and less than or equal to 0.354, and its carbon content is greater than 0 and less than or equal to 6.2 weight %.

2. The lithium-containing precursor of the positive electrode material according to claim 1, characterized in that: The carbon content is 0.05 wt % to 2.0 wt %.

3. The lithium-containing precursor of the positive electrode material according to claim 1 or 2, characterized in that: The chemical formula Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , 0.50≤x≤0.90, 0.01≤y≤0.

40.

4. The lithium-containing precursor of the positive electrode material according to claim 3, characterized in that: The chemical formula Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , 0.55≤x≤0.80, 0.05≤y≤0.20, 0.08≤1-xy≤0.

30.

5. The lithium-containing precursor of the positive electrode material according to any one of claims 1 to 4, characterized in that: The chemical formula Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , 0.10≤a≤0.50 or 1<a≤1.

08.

6. The positive electrode material lithium-containing precursor according to any one of claims 1 to 5, characterized in that: The chemical formula Li a (Ni x Co y Mn 1-x-y )O2(Li2CO3) z 0.05≤z≤0.

20.

7. The lithium-containing precursor of the positive electrode material according to any one of claims 1 to 6, characterized in that: The positive electrode material lithium-containing precursor includes at least one sheet-like agglomerate formed by agglomeration of primary particles.

8. The positive electrode material containing lithium precursor according to claim 7, characterized in that: The maximum thickness of the flake agglomerate is 0.1 to 7 μm, the maximum length is 0.1 to 19 μm, and the maximum width is 0.1 to 19 μm.

9. The lithium-containing precursor of the positive electrode material according to claim 7 or 8, characterized in that: The positive electrode material lithium-containing precursor comprises at least two sheet-like aggregates, and there are gaps between the sheet-like aggregates, and the gaps are in the range of 1 nm to 1 μm.

10. The lithium-containing precursor of the positive electrode material according to claim 7, characterized in that: The particle size of the primary particles is less than or equal to 100 nanometers.

11. The lithium-containing precursor of the positive electrode material according to any one of claims 1 to 10, characterized in that: In the powder X-ray diffraction pattern using Cu-Kα radiation, there is a diffraction peak at 31.7±0.3 degrees 2θ.

12. The lithium-containing precursor of the positive electrode material according to claim 11, characterized in that: The powder X-ray diffraction pattern using Cu-Kα rays has diffraction peaks at 18.6±0.3, 21.2±0.3, 30.5±0.3, 31.7±0.3, 36.4±0.3, 38.0±0.3, 44.1±0.3, 48.4±0.3, 58.3±0.3, 64.2±0.3, and 67.7±0.3 degrees 2θ.

13. The lithium-containing precursor of the positive electrode material according to claim 11 or 12, characterized in that: In the powder X-ray diffraction pattern using Cu-Kα radiation, the peak intensity I a The peak intensity I b The ratio is greater than or equal to 0.2 and less than 1.

0.

14. The lithium-containing precursor of the positive electrode material according to claim 13, characterized in that: In the powder X-ray diffraction pattern using Cu—Kα rays, the ratio of the half-peak width α of the peak existing at 18.6±0.3 degrees 2θ to the half-peak width β of the peak existing at 44.1±0.3 degrees 2θ is 1.1 to 1.

4.

15. The positive electrode material lithium-containing precursor according to claim 14, wherein in the powder x-ray diffraction pattern using Cu-Kα rays, the half-peak width α of the peak at 18.6±0.3 degrees 2θ is 0.60-0.80 degrees, and the half-peak width β of the peak at 44.1±0.3 degrees 2θ is 0.40-0.60 degrees.

16. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The ratio of the tap density to the bulk density of the lithium-containing precursor of the positive electrode material is greater than 2.

17. The lithium-containing precursor of the positive electrode material according to claim 16, characterized in that: The tap density is 0.8 to 2.5 g / cm 3 The bulk density is 0.4 to 0.9 g / cm 3 .

18. The lithium-containing precursor of the positive electrode material according to claim 1, characterized in that: The positive electrode material lithium-containing precursor has a D90 / D10 value of 4 or more and 12 or less, which is obtained from a particle size distribution measurement.

19. The lithium-containing precursor of the positive electrode material according to claim 18, characterized in that: The D90 is 5 to 38 μm, and the D10 is 0.5 to 7.6 μm.

20. The lithium-containing precursor of the positive electrode material according to claim 1, characterized in that: The D90 / D50 value of the positive electrode material lithium-containing precursor obtained from the particle size distribution measurement value is 1.5-5.

21. The lithium-containing precursor of the positive electrode material according to claim 20, characterized in that: D90 is 5 to 38 μm, and D50 is 1.0 to 12 μm.

22. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The ratio of the specific surface area of ​​the lithium-containing precursor of the positive electrode material to D50 is 3×10 6 ~15×10 6 m / g.

23. The lithium-containing precursor of the positive electrode material according to claim 22, characterized in that: The specific surface area of ​​the positive electrode material containing lithium precursor is 2 to 20 m 2 / g.

24. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The calcium ion content in the lithium-containing precursor of the positive electrode material is less than 500 ppm.

25. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The magnesium ion content in the lithium-containing precursor of the positive electrode material is less than 500 ppm.

26. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The sulfate content in the lithium-containing precursor of the positive electrode material is below 50 ppm.

27. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The sodium ion content in the lithium-containing precursor of the positive electrode material is below 50 ppm.

28. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The contents of hydrochloride, phosphate and oxalate in the lithium-containing precursor of the positive electrode material are all below 100 ppm.

29. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The crystal structure of the lithium-containing precursor of the positive electrode material is a layered structure.

30. The positive electrode material lithium-containing precursor according to claim 29, characterized in that: The crystal form of the lithium-containing precursor of the positive electrode material is one or more of spinel, cubic and octahedral types.

31. The positive electrode material lithium-containing precursor according to claim 1, characterized in that: The positive electrode material contains a lithium precursor with a charge and discharge voltage of 3.0 to 4.4 V and a 0.1C first discharge capacity of less than 130 mAh / g.

32. The positive electrode material lithium-containing precursor according to claim 31, characterized in that The positive electrode material contains a lithium precursor, and the charge and discharge voltage is 3.0 to 4.4 V, and the capacity of the 0.1C first discharge is 10 to 68 mAh / g.

33. A method for preparing a lithium-containing precursor of a positive electrode material as claimed in any one of claims 1 to 32, comprising the following steps: preparing a mixed solution of lithium nitrate, nickel nitrate, cobalt nitrate and manganese nitrate; The mixed solution is subjected to atomization calcination treatment to obtain a lithium-containing precursor of the positive electrode material. The temperature of the atomization calcination treatment is 400° C.-1000° C., and the air-to-coal ratio of the calcination furnace is less than or equal to 10.

34. A positive electrode material, characterized in that The positive electrode material is formed by sintering the positive electrode material lithium-containing precursor according to any one of claims 1 to 32.

35. A positive electrode material according to claim 34, characterized in that: The free lithium content of the positive electrode material is less than 1000 ppm.

36. A positive electrode material according to claim 35, characterized in that: The first coulombic efficiency of the positive electrode material is greater than 90.

37. A method for preparing a positive electrode material, characterized in that: The method comprises keeping the positive electrode material lithium-containing precursor of any one of claims 1 to 32 at a first temperature of 400° C. to 800° C. for 1 to 5 hours, and keeping it at a second temperature of 800° C. to 1050° C. for 5 to 10 hours.

38. A lithium secondary battery, characterized in that: The lithium secondary battery includes the positive electrode material according to any one of claims 34 to 37.

Citation Information

Cited By

  • Lithium-containing precursor of positive electrode material and preparation method therefor, positive electrode material, and lithium secondary battery

    EP4717674A1

  • Lithium-containing precursor of positive electrode material and preparation method therefor, positive electrode material, and lithium secondary battery

    WO2025002077A1